Changes in plasma and urine globotriaosylceramide levels do not predict Fabry disease progression over 1 year of agalsidase alfa - Schiffmann, Raphael; Ries, Markus; Blankenship, Derek; Nicholls, Kathy; Mehta, Atul; Clarke, Joe T. R.; Steiner, Robert D.; Beck, Michael; Barshop, Bruce A.; Rhead, William; West, Michael; Martin, Rick; et al. (Genetics in medicine, 2013)
Purpose: Globotriaosylceramide concentrations were assessed as potential predictors of change from baseline after 12 months by estimated glomerular filtration rate and left-ventricular mass index using pooled data from three randomized, placebo-controlled agalsidase alfa trials and open-label extensions of patients with Fabry disease. Methods: Males (aged 18 years or older) with Fabry disease received agalsidase alfa (0.2 mg/kg every other week for 12 months). A backward-elimination approach evaluated potential predictors (baseline estimated glomerular filtration rate and left-ventricular mass index; age at first dose; baseline and change from baseline at 12 months of globotriaosylceramide (urine, plasma); urine protein excretion; and systolic and diastolic blood pressure). Subgroups included patients randomized to placebo or agalsidase alfa (double-blind phase), then to agalsidase alfa (open-label extensions. Results: Baseline estimated glomerular filtration rate, age at first dose, baseline urine globotriaosylceramide excretion, and baseline and change from baseline urine protein excretion significantly predicted change from baseline estimated glomerular filtration rate in the analysis population (N = 73; all P<0.05), although not in all subgroups. Change from baseline urine and plasma globotriaosylceramide (baseline and change from baseline) concentrations did not predict change from baseline estimated glomerular filtration rate. No predictors of left-ventricular mass index were significant. Conclusion: Changes in globotriaosylceramide concentrations do not appear to be useful biomarkers for prediction of Fabry disease–related changes in estimated glomerular filtration rate or left-ventricular mass index.
Gesehen am 24.06.2021